Comparative effect of curcumin and nanocurcumin on nephroprotection at cisplatin-induced rats - Ni Made D Sandhiutami; Wawaimuli Arozal; Melva Louisa; Deni Rahmat; Tjoeng Mandy (Wolters Kluwer Medknow Publications, 2019)
Background: Cisplatin is a first-line chemotherapeutic agent for various solid tumors including ovarian and breast cancer. Thereby, it has been proven effective as an antineoplastic agent, but its clinically use is limited because of its nephrotoxicity side effect. Aims and Objectives: This study aimed to investigate curcumin as a renoprotector agent against cisplatin nephrotoxicity. Materials and Methods: The samples used were curcumin and its nanoparticles formulated using ionic gelation method. The nephrotoxicity was investigated through several parameters such as serum creatinine, blood urea nitrogen, serum albumin, kidney weight ratio, and histopathology. These parameters were tested on rats and divided into the following four groups: normal group, negative control group that administered cisplatin with doses amount of 7 mg/kg body weight (BW) intraperitoneally, nanocurcumin group (cisplatin + nanocurcumin) and curcumin group (cisplatin + curcumin). The agents were administered at a dose of 100 mg/kg BW every day in 9 days before cisplatin administration. The sample of blood serum and kidneys organ were taken 48h after cisplatin administration. Results: The negative control group showed a significant increase in serum creatinine, blood urea nitrogen, and kidney weight ratio, whereas it showed a significant decrease in serum albumin. The administration of sample agents showed a significant decrease in serum creatinine, blood urea nitrogen, and kidney weight ratio and an increase in the albumin level as compared to negative control group. Conclusion: Nanocurcumin showed significant improvement in kidneys more than curcumin. In contrast, histopathological examination verified the necrosis in negative control group, suggesting the renoprotection effect of nanocurcumin against nephrotoxicity on cisplatin-induced rats.